ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI SEBAGAI DASAR PENETAPAN HARGA JUAL DIVERSEN UNIT KALIDONI PALEMBANG - Rizal Effendi; Lili Syafitri (JURNAL KOMPETITIF, 2020)
To calculate the cost of goods manufactured, the analytical tool used is the full costing method. This research is aimed to find out how to calculate the cost of water production in the Tirta Musi Palembang PDAM in the 2016-2017 period, to find out how to calculate the selling price at the Tirta Musi Palembang PDAM in the 2016-2017 Period, and to find out how to calculate the cost of production as the basis for determining prices sell at PDAM Tirta Musi Palembang. This research method uses secondary data, with descriptive research, the research method used is case studies, and the research uses qualitative and quantitative descriptive methods. The results showed the cost of production in 2016-2017 PDAM Tirta Musi Palembang, seen increasing every year. This happened because of an increase in total business costs. The cost of production in 2016 is Rp. 661,886,491 and the cost of production in 2017 of Rp. 699,585,427. the selling price in 2016-2017 shows that the selling price experienced an increase. PDAM Tirta Musi Palembang in calculating water tariffs using a basic rate. In 2016 the basic tariff of Rp. 4097.14 cubic meters, and in 2017 Rp. 4,579.28 cubic meters. It appears that the company is making a profit.Keywords: Cost Accounting, Cost of Production and Selling Prices